Proceedings of the 22nd International Conference on Auditory Display - ICAD 2016 2016
DOI: 10.21785/icad2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Towards An In-Vehicle Sonically-Enhanced Gesture Control Interface: A Pilot Study

Abstract: A pilot study was conducted to explore the potential of sonically-enhanced gestures as controls for future in-vehicle information systems (IVIS). Four concept menu systems were developed using a LEAP Motion and Pure Data: (1) 2x2 with auditory feedback, (2) 2x2 without auditory feedback, (3) 4x4 with auditory feedback, and (4) 4x4 without auditory feedback. Seven participants drove in a simulator while completing simple target-acquisition tasks using each of the four prototype systems. Driving performance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Both studies report different observations regarding eyes-off-the-road time and perceived mental workload. Sterkenburg et al [35] found a significant difference in eyes-off-the-road time and mental demand between the visual and visual-auditory condition, which is contrary to May et al's [25] findings. Thus, research is still required in order to address these questions sufficiently.…”
Section: Auditory Displaysmentioning
confidence: 70%
See 2 more Smart Citations
“…Both studies report different observations regarding eyes-off-the-road time and perceived mental workload. Sterkenburg et al [35] found a significant difference in eyes-off-the-road time and mental demand between the visual and visual-auditory condition, which is contrary to May et al's [25] findings. Thus, research is still required in order to address these questions sufficiently.…”
Section: Auditory Displaysmentioning
confidence: 70%
“…Sterkenburg et al [35] observed significant reductions in eyesoff-the-road time their visual and auditory conditions. They conducted a pilot study on the potential of auditory feedback for in-air gesture control in vehicles.…”
Section: Auditory Displaysmentioning
confidence: 97%
See 1 more Smart Citation
“…May et al [32] found that mental demand did not increase nor did driving performance decrease compared to direct touch interaction when auditory and visual feedback were presented bimodally. Sterkenburg et al [43,42] also explored bi-modal audio-visual feedback for gesture control and found that it led to significantly less eyes-off-the-road time and lane deviation than uni-modal visual feedback. However, May et al [32] and Sterkenburg et al [43,48] presented visual feedback in their bi-modal conditions continuing to present information to a channel which is fully occupied by the primary driving task.…”
Section: Related Workmentioning
confidence: 99%
“…Auditory feedback in driving environments has been shown to reduce looking away time [10] and if presented to mid-air gestures it reduces eyes-off-the-road time without negatively impacting the driving performance [41,43] nor mental demand [41,32]. A multimodal combination of ultrasound and audio feedback can surpass the shortcomings of ultrasound haptics for mid-air feedback [8].…”
Section: Auditory Feedbackmentioning
confidence: 99%